Síntese e avaliação anti-tripanossoma e citotóxica de benzaldeído-tiossemicarbazonas derivadas do ácido caurenóico - Haraguchi, Shirani Kaori (2008)
In the search for compounds with antitumoral and parasiticide activities, and considering that the great majority of the thiosemicarbazones described in the literature presents structural variations just in iminic carbon, our research group began the synthesis of new thiosemicarbazones derivatives of natural products containing a monoterpenic unit linked to terminal nitrogen. And, giving continuity to the project, the research was extended for the synthesis of new thiosemicarbazones derivatives of diterpene. The present work describes the synthesis of new thiosemicarbazones substituted in its iminic carbon with a phenyl moiety or phenyl substituted and its terminal nitrogen with a diterpenic unit, the kaurenoic acid that was isolated of the species Croton floribundus (Euphorbiaceae). The benzaldehyde-thiosemicarbazones derivatives of the kaurenoic acid were synthesized, yielding between 60 and 96%, through the condensation between the corresponding thiosemicarbazide and the benzaldehyde and its derivatives substituted in para with methyl, methoxyl, hydroxyl and dimethylamine moieties and in ortho, meta and para with nitro and chloro moieties. In the same way, the thiosemicarbazide was obtained, with 82% of yield, by the reaction between hydrazine and its respective isothiocyanate that was obtained with 58% of yield by the reaction between kaurenoic acid and isothiocyanic acid. All synthesized compounds, with exception of the thiosemicarbazide and p-nitro-benzaldehyde-thiosemicarbazone synthesized, were more active than kaurenoic acid against epimastigote form of Trypanosoma cruzi, standing out the o-nitro-benzaldeído-thiosemicarbazone with IC50 of 2 μM. The synthesized compounds present significant toxicity on the cells LLMCK2 and the smallest toxic effects were presented by p-dimethylamine-benzaldehyde-thiosemicarbazone and o-chloro-benzaldehyde-thiosemicarbazone. Therefore, the benzaldehyde-thiosemicarbazones derivatives of kaurenoic acid showed an increase of the anti-trypanosomal activity when compared to the kaurenoic acid, without significant diminishing of their cytotoxic values for the tested cells. However, the high cytotoxicities expressed by the same ones are indications of these as potential anticancer agents.